2016
DOI: 10.1177/8755123315626229
|View full text |Cite
|
Sign up to set email alerts
|

Managing Student Behavior in an Elementary School Music Classroom: A Study of Class-Wide Function-Related Intervention Teams

Abstract: Classroom management is a common concern for teachers. Music teachers in particular experience unique behavior challenges because of large class sizes, uncommon pacing requirements, and performance-based outcomes. Positive behavior support is an evidence-based framework for preventing or eliminating challenging behaviors by teaching and reinforcing appropriate social skills. Class-Wide Function-Related Intervention Teams (CW-FIT), a specific positive behavior support intervention involving social skills instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…However, the fourth-grade teacher’s reprimand rates were higher with CW-FIT; she gave more reprimands during the intervention condition, but she also gave more statements of praise, communicating more with her class concerning their behavior during the intervention phase. In addition, results showed that when CW-FIT was reintroduced following reversal in the second- and third-grade classrooms, reprimand rates tended to increase, similar to results of a CW-FIT study conducted in a music classroom (Caldarella, Williams, Jolstead, & Wills, 2016). It is unclear why reprimand rates tended to be more inconsistent than in other CW-FIT studies, which have shown more predictability (Caldarella et al, 2015; Kamps et al, 2011; Wills et al, 2010).…”
Section: Discussionsupporting
confidence: 66%
“…However, the fourth-grade teacher’s reprimand rates were higher with CW-FIT; she gave more reprimands during the intervention condition, but she also gave more statements of praise, communicating more with her class concerning their behavior during the intervention phase. In addition, results showed that when CW-FIT was reintroduced following reversal in the second- and third-grade classrooms, reprimand rates tended to increase, similar to results of a CW-FIT study conducted in a music classroom (Caldarella, Williams, Jolstead, & Wills, 2016). It is unclear why reprimand rates tended to be more inconsistent than in other CW-FIT studies, which have shown more predictability (Caldarella et al, 2015; Kamps et al, 2011; Wills et al, 2010).…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies of CW-FIT in elementary grades have consistently shown improved prosocial behavior and reduced disruptive behavior during instruction as well as increased rates of teacher praise and decreased reprimands across age groups and subject areas (Caldarella, Williams, Hansen, & Wills, 2015;Caldarella, Williams, Jolstead, & Wills, 2017;Kamps et al, 2015Kamps et al, , 2011Weeden, Wills, Kottwitz, & Kamps, 2016;Wills, Iwaszuk, Kamps, & Shumate, 2014;Wills et al, 2010). The intervention has also been found to yield high levels of treatment integrity and to be perceived by teachers and students as being socially valid .…”
Section: Review Of Previous Researchmentioning
confidence: 79%
“…Researchers chose dependent variables and measures based on previous CW-FIT studies so results could be compared (Caldarella et al, 2017;Wills et al, 2019Wills et al, , 2016. Data were collected for (a) on-task behavior of all students in the class, (b) on-task behavior of the students identified as at risk for EBD, (c) disruptive behavior of the at-risk students, and (d) teacher praise and reprimand rates.…”
Section: Dependent Variables and Measuresmentioning
confidence: 99%
“…Although results of CW-FIT have been positive in general education classrooms, less research has been conducted in nontraditional or specialty classes where behavior has been found to vary (Jason & Kuchay, 1985). CW-FIT has been effective in an elementary music classroom (Caldarella, Williams, Jolstead, & Wills, 2017) during elementary physical education sessions (Hirsch, Healy, Judge, & Lloyd, 2016), and in preschool classrooms (Jolstead et al, 2017). However, investigations of CW-FIT in art classrooms have not occurred, despite art teachers' reports of feeling overwhelmed and unprepared to manage problem behavior.…”
Section: Cw-fitmentioning
confidence: 99%